Obligatory reflexivity in a Minimalist grammar of Afrikaans - Oosthuizen, Johan (Stellenbosch Papers in Linguistics Plus, 2014)
This paper deals with the phenomenon of obligatory reflexivity in Afrikaans. Adopting the general framework of Minimalist Syntax, an attempt is made to develop a novel analysis of this phenomenon that can provide a conceptually adequate account for the facts, and that is amenable to extension beyond Afrikaans. The basic idea underlying the proposed “nominal shell analysis (of obligatory reflexivity)” (NSA) is that two expressions which enter into an obligatory coreferential relationship – in this case, the reflexive and its antecedent – are initially merged into the same constituent. It is proposed that these two expressions form part of a nominal shell structure which is headed by an identity focus light noun n, a functional category which belongs to a natural class of identificational (or quantificational) elements. This n represents the locus of the –self suffix that is normally found with reflexive pronouns in Afrikaans. The coreferential relationship between the reflexive and its antecedent is established in this nominal shell via phi(φ)-feature valuation, with the light noun acting as intermediary. It is claimed that the NSA can provide an empirically adequate account of the relevant facts without appealing to any theoretical devices or features that are not provided by or that are incompatible with the basic assumptions and concepts of Minimalist Syntax.